Potret Peristiwa Tindak Tutur dalam Kegiatan Forum Kerukunan Umat Beragama (FKUB) Lampung Timur - Ani Susilowati; Akhadiyatus Sholihah (Institut Agama Islam Negeri (IAIN) Metro, 2018)
This study describes the portrait of speech acts in the East Lampung religious harmony forum. The aim of this research is to know the portrait of the speech act in the activities of the Religious Harmony Forum (FKUB) in East Lampung. The type of this research is qualitative research that uses a pragmatic approach by applying descriptive qualitative methods. This method is used to describe speech events and speech acts based on the data that has been collected by the writer. To complete the data the writer uses listening technique method and proficient technique. From the two methods the writer uses several techniques, namely instruments, recording technique and writing technique. After extracting the data, the next step is processing and analyzing data by using the following steps; the first data transcript containing the speech act which is transcribed into written language. Second puts the results of the data into the data card. Third, the writer analysis the data based on several aspects that has done by the writer. Fourth, the classification of the data based on the type of speech events and speech acts. Based on the results of the research data analysis, it can be concluded that the speech acts used in the Forum of Religious Harmony are locution of speech acts, perlocution of speech acts, and illocution of speech acts which have four forms, namely 1) assertive (declaring, suggesting, reminding). 2) directive (rule, recommend). 3) expressiveness (thanking, apologizing, condolence). 4) commissive (offering something).